Biotransformation of Zerumbone and Goniothalamin by Aspergillus Niger (Ftcc 5003) and Sclerotium Rolfsii (Local Isolated): Structural Elucidation and Biological Activities - Chia, Poh Wai (2008)
Microbial transformation was carried out on three natural product compounds, namely zerumbone, goniothalamin and cardamonin, using the fungi Aspergillus niger and Sclerotium rolfsii. Aspergillus niger and Sclerotium rolfsii have successfully converted zerumbone into two products, namely 2,3-dihydrozerumbone and 6,7-epoxyzerumbone. Aspergillus niger and Sclerotium rolfsii also successfully biotransformed goniothalamin into 2,3-dihydrogoniothalamin. The trial carried out on cardamonin was unsuccessful due to the antimicrobial activity of the compound that inhibited the growth of the fungi. Sclerotium rolfsii is a newly discovered biotransformer able to carry out hydrogenation and epoxidation. Two microbial toxins, namely gliotoxin and bisdethiobis(methylthio)gliotoxin were isolated in the course of biotransformation of goniothalamin using A. niger and S. rolfsii cultured on PKC (Palm Kernel Cake) media. The toxins were not produced when the biotransformation was repeated using fungi cultured on standard glucose media. Thus, PKC was deduced to be conducive to the production of the toxins by the two fungi. In an attempt to isolate and purify marchantin A as a candidate for biotransformation studies, several compounds which included marchantin A, apigenin, luteolin and a mixture of stigmasterol and β-sitosterol were found.. A preliminary antiinflammatory and anticholinesterase activities screening of the isolated compounds (zerumbone, 2,3-dihydrozerumbone, 6,7-epoxyzerumbone, goniothalamin, 2,3-dihydrogoniothalamin, gliotoxin, bisdethiobis(methylthio)gliotoxin, apigenin, luteolin, marchantin A and mixture of β-sitosterol and stigmasterol, were also conducted. Luteolin exhibited strong inhibition of soybean lipoxygenase with an IC50 value of 6.25 μg/ml while zerumbone showed moderate inhibition against soybean lipoxygenase with an IC50 value of 22.83 μg/ml. The other compounds were inactive towards the enzyme. In the anticholinesterase inhibitory assay, zerumbone, 6,7-epoxyzerumbone, marchantin A, goniothalamin, apigenin and luteolin, as well as a mixture of β-sitosterol and stigmasterol were found to inhibit the enzyme.